Fair Value Measurement in Saudi Arabia and its Expected Impact: A Special Focus on the Insurance Sector - Raj Bahadur Sharma , Nabil Ahmed M. Senan (International Journal of Advanced Science and Technology, 2020)
There is an ongoing debate in the world regarding valuing the assets at their historical cost or at the fair value measurement. The fair value measurement has been explained under Standard 13 of International Financial Reporting Standards (IFRS), providing a single framework to measure fair value and associated disclosures. The adoption of fair value accounting in all the companies for equity as per IAS 16, IAS 38, IAS 40 and IFRS 13 in the Kingdom of Saudi Arabia (KSA) is under consideration by Saudi Organization for Certified Public Accountants (SOCPA), Saudi Arabian Monetary Authority (SAMA) and Capital Market Authority (CMA), but allowed in banking and insurance sectors. The Saudi Arabian companies might achieve several benefits in adopting the IFRS framework and also revaluing the equity and marketable securities. according to fair value measurement. Hence, the current study assesses the expected effect of fair value measurement on the companies’ financial statements in the insurance sector. Data Envelopment Analysis (DEA) was used to measure the efficiency of the two methods of accounting, i.e. the historical cost method and fair value method. Even though there are policy issues that might hinder the adoption of fair value accounting by the companies, since IFRS is more comprehensive compared to Saudi standards, it is found that the adoption is enhancing the reporting standards in KSA.